Effect of humidity and temperature on the survival of Listeria monocytogenes on surfaces. (1st April 2017) - Redfern, J.; Verran, J.
Abstract : Abstract: Listeria monocytogenes is a pathogenic bacterium, with human disease and infection linked to dairy products, seafood, ready‐to‐eat meat and raw & undercooked meats. Stainless steel is the most common food preparation surface and therefore, it is important to understand how food storage conditions such as surface materials, temperature and relative humidity can affect survival of L. monocytogenes . In this study, survival of L. monocytogenes on stainless steel was investigated at three temperatures (4, 10 and 21°C), each approx. 11, 50 and 85% humidity. Results indicate that the lower the temperature, the more cells were recovered in all three humidity environments, while medium humidity enhances survival, irrespective of temperature. Lower humidity decreases recovery at all temperatures. These data support the guidance noted above that humidity control is important, and that lower humidity environments are less likely to support retention of viable L. monocytogenes on a stainless steel surface. Significance and Impact of the Study: Understanding survival of potential food‐borne pathogens is essential for the safe production and preparation of food. While it has long been 'common knowledge' that relative humidity can affect the growth and survival of micro‐organisms, this study systematically describes the survival of L. monocytogenes on stainless steel under varying humidity and temperatures for the first time. The outcomes from this paper will allow those involved with food manufacture and preparation to make informed judgement on environmental conditions relating to humidity control, which is lacking in the food standards guidelines.